Analisis Potensi dan Pemanfaatan Sumberdaya Ikan (SDI) Yang Didaratkan di Pelabuhan Perikanan Teluk Awang - Sadikin Amir; Sitti Hilyana; Saptono Waspodo; Soraya Gigentika; Edwin Jefri (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2021)
The Teluk Awang Fishery Port (PP) is located in Mertak Village, Central Lombok Regency, which has the potential to develop as a center of economic growth with a fishery business base. It has a good geographical location because it is protected from waves coming from the Indian Ocean. Currently the Central Government, West Nusa Tenggara Provincial Government and Central Lombok Regency Government are jointly developing Awang Bay as a fishery business center by building a fishing port that can accommodate fishing vessels operating in WPPNRI 573 and 713. This study will look at fish resources ( SDI) in PP Teluk Awang uses the Participatory Action Research (PAR) method which actively involves all relevant parties. The results of the research show that the SDI that was landed in PP Teluk Awang during 2018-2020 as much as 3,559,483 kg was still dominated by pelagic and demersal fish, such as Cakalang fish (62.67%), Layang (10.77%), Tongkol ( 8.29%), Lemadang (6.34%), Tuna (5.42%), Baby Tuna (3.88%), Marlin (1.48%) and other fish (1.15%). The recorded fleet of ships is 27 units with a size of 8-25 Gross Tonnage (GT). The results of this study are expected to be a recommendation related to policies in managing the potential of SDI landed in PP Teluk Awang with the concept of sustainable fisheries.